Cytotoxic, Anti-Microbial and Anti-Alzheimer Potential of Ferulago stellata Boiss. Fruits and Its Chemical Composition - Yahya Rahimpour; Abbas Delazar; Samad Nejad Ebrahimi; Mahsa Sabernavaei; Parina Asgharian* (Iranian Society of Pharmacognosy, 2022)
Background and objectives: The Ferulago species are perennial aromatic plants and have been used as digestive, flavoring, sedatives, and aphrodisiac agent. Methods: The volatile oil from Ferulago stellata fruits was attained through hydrodistillation methods using a Clevenger-type apparatus. Then, the chemical composition was assessed by gas chromatography mass spectrometry (GC-MS). The antioxidant activity of the volatile oil was evaluated by the DPPH method. The extracts were sequentially obtained by the Soxhlet apparatus with different solvents. To analyze the fatty acid profile, the non-polar extract (n-hexane) was converted to the corresponding methyl ester via saponification and esterification and assessed by GC. The antimicrobial activity of the volatile oil and extracts were evaluated against eight microorganisms and MIC and MBC were attained by the micro broth dilution method. The antiproliferative and acetylcholinesterase inhibitory activity of the extracts was evaluated as well. Results: Fourteen volatile constituents were identified of which the main constituent was 2,4,6-trimethyl benzaldehyde (56.05%). The essential oil indicated high antioxidant activity with IC50 value of 6.05 ± 0.77 μg/mL. The volatile oil showed powerful antimicrobial activity against all strains of the microorganisms with MIC 0.78 to 3.12 µg/mL and MBC between 1.56 and 6.25 µg/mL. The n-hexane extract showed higher cytotoxicity effect compared to other extracts. The result of the fatty acid profile demonstrated that the fruits were rich source of unsaturated fatty acids. Conclusion: F. stellata might be a potent source of antioxidant, antimicrobial, and healthy fatty acid which can be used in the pharmaceutical, cosmetic, and food industries.